A limestone landscape from the air : le Causse Méjean, Languedoc, France - Fowler, Peter
Reconnaissance on the southern edge of the Massif Central is studying field evidence which deepens appreciation of the present-day upland French landscape as not only 'sauvage' but also the product of long-term use.